TINGKAT KEPUASAN MAHASISWA FAKULTAS FARMASI TERHADAP PELAYANAN VAKSINASI COVID-19 (DOSIS 1 DAN 2) DI KABUPATEN KARAWANG - Lina Aliyani Mardiana; Ady Yusup Harian Jaya; Dian Iftihar Sulaiman; Husnain M Mahlup; Ika Oktaviyanti Lutfah; Muhammad Rifqi Ardian; Rasiman Julianto; Rifaldi Mardiansyah; Silky Maulina; Theshinta Berliana Widjaya; Tri Yuni Rahayu; Umar Bahrudin (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
The outbreak of Corona Virus Disease 2019 or referred to as Covid-19 that hit the world in 2020 and started from Wuhan, China caused emergencies in various countries, one of which was Indonesia. With the Covid-19 pandemic, the government has set policies to limit all community activities that can allow the transmission of Covid-19. Another policy implemented by the government to reduce the surge in Covid-19 cases is to provide Covid-19 vaccines to all Indonesian citizens. This study is a quantitative study using a questionnaire that was conducted in May - June 2022. This study was taken from someone who has vaccinated against Covid-19, this data collection was carried out to determine a person's level of satisfaction with the services received when vaccinating. The sample of this study consisted of UBPK pharmacy students and UNSIKA pharmacy students in Karawang district. Respondents' identities were based on gender, age, institution of origin, status (college while working), status (married), vaccination sites 1 and 2, complaints felt after vaccination, confidence after vaccination 1 and 2. Based on the results of the Covid-19 vaccination satisfaction survey in the Karawang district during the Covid-19 pandemic, data were obtained with a high consumer satisfaction value, very high interpretation (81%-100%), and an average percentage value of five dimensions of high service quality, namely 97.9%. The five dimensions of service quality are equal to or above 81%, namely tangibles, reliability, responsiveness, assurance and empathy. The highest service quality is at 99% empathy dimension and the lowest is 96% reliability dimension.